Efficacy and Tolerability of Intranasal use of Viferon for Acute Respiratory Viral Infections in Children - Ryder W. Sharpe, Alfred B. Booth, Balfour F. Rupert (Open Journal of Physicians and Surgeons, 2024)
The study of Viferon in the management of Acute Respiratory Tract Infections in children showed significant improvement in efficacy and tolerance with special emphasis on the intranasal administration of Viferon. Viferon (recombinant human interferon alpha-2b) is used intranasally to enhance the local and systemic targeting of viral pathogens. According to the research, Viferon not only tends to hasten the general period of disease but also has a shortening effect on the duration and severity of coldrelated symptoms. When children who were being treated with Viferon were compared with control groups who only received standard treatment, improved clinical parameters such as reduction of fever and relieving cough were noticed. Overall, Viferon therapy was well tolerated and poorly adverse events were experienced among the pediatric respondents. It needs to be emphasized that this problem is more relevant for the outpatient department, where intranasal Viferon is being proposed as an alternative therapeutic agent for ARVI in children. All the same, the findings indicate that Viferon can be used as an additional treatment along with conventional treatment of ARI in children resulting in their faster recovery and lesser use of systemic drugs.